Navigating the trade landscape: A Latin American perspective building on the WTO 13th ministerial conference - Piñeiro, Valeria; Campos Azofeifa, Adriana; Piñeiro, Martin (International Food Policy Research Institute, 2024)
This publication-a joint effort by the International Food Policy Research Institute (IFPRI) and the Inter-American Institute for Cooperation on Agriculture (IICA)-is being released in the context of growing changes and fragmentation in global economic and trade relationships. Countries are increasingly adopting protectionist measures in response to recent crises and the decreased competitiveness of value chains, due to rising production, marketing and transportation costs. The complex multilateral trade system and the urgent need to implement concrete actions in this area are prompting countries to work towards the adoption of new standards that aim to protect and preserve the environment but could also become barriers to trade that impose a significant economic and social cost on other countries. The countries of the Americas must continue to support efforts to strengthen the multilateral trade system, ensuring that it is open, transparent and science-based, as well as to effectively participate in discussion forums such as the ministerial conferences of the World Trade Organization (WTO). Amidst this scenario, international trade plays a vital role in transforming food systems, by interconnecting them and contributing to creating a more sustainable global food system. In recent years, the growth of production and exports has converted Latin America and the Caribbean (LAC) into the largest net food exporting region in the world. On average, agrifood exports from the region in 2021-2023 accounted for 17% of global agrifood exports, representing one fourth of total exports from the region. During that period, LAC agrifood exports grew by 7.6%. Yet, it bears mentioning that, despite its important role, the region has its share of challenges. During 2023, 85% of LAC agrifood exports were directed at external markets and 53% of the value of exported agrifood exports was concentrated among only 10 products. This demonstrates the region’s significant vulnerability and is undoubtedly a challenge that must be addressed. This document is an inter-institutional effort to share ideas and reflections on the main issues to be tackled building on the 13th WTO Ministerial Conference. We hope that it will serve as input in strengthening the participation of the countries of the Americas in WTO multilateral negotiations, while also highlighting the key role of agricultural trade in agrifood system transformation.